Pengaruh pendidikan kesehatan terhadap tingkat pengetahuan dan sikap remaja sma x dalam upaya pencegahan hiv/aids di kabupaten karanganyar - Muliana, Maria; , Noor Alis Setiyadi, SKM., MKM., Dr.Ph; , Kusuma Estu Werdani, SKM., M.Kes (2014)
AIDS (acquired Immuno Deficiency Syndrome) is a collection of diseases caused by the virus HIV (Human Immunodeficiency Virus) is a contagious and deadly. This virus damages the immune system of the human body resulting in immune deficiencies. Karanganyar an area that statistically increased cases of HIV / AIDS. Need of prevention in improving adolescent knowledge and attitudes by providing health education and health promotion. This study aims to determine whether there is an influence of health education on the level of knowledge and attitude of high school adolescents in the prevention of HIV / AIDS in Karanganyar. This research is a experiment research desaign the form of Pre-test Post-test Control Group. The subjects were students of class XI with a population of 168, including 65 experimental group students and 65 students with a control group using a sampling technique Proporsional Random Sampling. Analysis of the data used paired sample T-test and Wilcoxon Signed Rank Test. The results showed no effect of health education on prevention of HIV / AIDS on the level of knowledge (p = 0.000) and attitude (p = 0.000) in the experimental group. Whereas in the control group there was no effect, with the value of knowledge (p = 0.157) and attitude (p = 0.083.)